Baicalein and Baicalin Inhibit SARS-CoV-2 RNA-Dependent-RNA Polymerase - Zandi, Keivan; Musall, Katie; Oo, Adrian; Cao, Dongdong; Liang, Bo; Hassandarvish, Pouya; Lan, Shuiyun; Slack, Ryan L.; Kirby, Karen A.; Bassit, Leda; Amblard, Franck; Kim, Baek; et al. (Microorganisms (Basel), 2021)
Coronavirus Disease 2019 (COVID-19) is a deadly emerging infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Because SARS-CoV-2 is easily transmitted through the air and has a relatively long incubation time, COVID-19 has rapidly developed into a global pandemic. As there are no antiviral agents for the prevention and treatment of this severe pathogen except for remdesivir, development of antiviral therapies to treat infected individuals remains highly urgent. Here, we showed that baicalein and baicalin exhibited significant antiviral activity against SARS-CoV-2, the causative agent of COVID-19 through in vitro studies. Our data through cell-based and biochemical studies showed that both compounds act as SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) inhibitors directly and inhibit the activity of the SARS-CoV-2 RdRp, but baicalein was more potent. We also showed specific binding of baicalein to the SARS-CoV-2 RdRp, making it a potential candidate for further studies towards therapeutic development for COVID-19 as a selective non-nucleoside polymerase inhibitor.